Seeking paradise in early twentieth-century Mindanao the Philippine experience of Vic Hurley - Luyt, Brendan (2025)
Vic Hurley worked in Mindanao in the interwar years. In this article I examine two of his nonfiction books, Southeast of Zamboanga (1935) and Men in Sun Helmets (1936). These books demonstrate how the discourse of tropics as paradise motivated Americans and Europeans to become colonialists. They also provide an example of why white settler colonialism failed in Mindanao, a failure that consequently enabled the rise of a Manila-based Filipino elite. Hurley’s depiction of colonialists not as heroes but as exiles also demonstrates the strengthening of a discourse that sought the separation of Filipinos and Americans based on supposedly fundamental racial differences.
Keywords: American colonialism